2014
DOI: 10.2147/ppa.s42145
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for ADHD: how do adolescent and adult patient beliefs and attitudes impact treatment adherence?

Abstract: Adherence to medication can be problematic for patients, especially so for patients with attention deficit hyperactivity disorder (ADHD). Effective medications are available for the treatment of ADHD; however, nonadherence rates for ADHD medication range from 13.2%–64%. The reasons for nonadherence can be complex. This review aims to look at how the beliefs and attitudes of adolescents and adults impact ADHD treatment adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Beliefs about the medication were divided into four main areas: (a) improved attention/academics (IAA), (b) loss of authentic self (LAS), (c) social self-enhancement (SSE), and (d) common side effects (CSE; Pillow et al, 2014). Pillow et al (2014) found that, similar to past research (McCarthy, 2014), the use of stimulant medication was seen as a trade-off, where the user is constantly balancing perceived costs and benefits. Participants who were currently taking medication believed that taking the medication would result in IAA and SSE.…”
supporting
confidence: 62%
“…Beliefs about the medication were divided into four main areas: (a) improved attention/academics (IAA), (b) loss of authentic self (LAS), (c) social self-enhancement (SSE), and (d) common side effects (CSE; Pillow et al, 2014). Pillow et al (2014) found that, similar to past research (McCarthy, 2014), the use of stimulant medication was seen as a trade-off, where the user is constantly balancing perceived costs and benefits. Participants who were currently taking medication believed that taking the medication would result in IAA and SSE.…”
supporting
confidence: 62%
“…Statistical assessment of PERMP total score (the primary endpoint) was conducted using a mixed linear model analysis of variance (ANOVA) for the average of classes 1 to 6 (postdose 2-16 h) and at each postdose class (2,4,8,12,14, and 16 h postdose). The model included sequence (placebo followed by 25 mg SHP465 MAS versus 25 mg SHP465 MAS followed by placebo), period (visit 4 versus visit 5), and treatment (placebo versus 25 mg SHP465 MAS) as fixed effects and participant within sequence as a random effect.…”
Section: Data Presentation and Statistical Analysismentioning
confidence: 99%
“…In addition, as is the case with other chronic disorders [12], medication adherence among adults with ADHD is negatively influenced by multiple factors that include forgetting to take medication (in part due to the executive function deficits that may be associated with ADHD [13]), the complexity of the treatment regimen (e.g. the need to take multiple medications or doses throughout the day), and the stigma associated with taking medication [14]. Taken together, these findings suggest some adults with ADHD may benefit from a once-daily medication with a duration of effect that allows them to more easily meet their specific, individualized environmental demands (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, nonadherence to treatment may range from 13.2% to 64.0% (McCarthy, 2014). Among the factors that concur to nonadherence are the lack of knowledge of ADHD, medication characteristics, and treatment goals (Charach & Fernandez, 2013).…”
Section: Palabras Clavementioning
confidence: 99%